2021
DOI: 10.1093/femsle/fnab121
|View full text |Cite
|
Sign up to set email alerts
|

The effects of captivity on the microbiome of the endangered Comal Springs riffle beetle (Heterelmis comalensis)

Abstract: The gut microbiome is affected by host intrinsic factors, diet, environment, and strongly linked to host's health. Although fluctuations of microbiome composition are normal, some are due to changes in host environmental conditions. When species are moved into captive environments for conservation, education, or rehabilitation, these new conditions can influence a change in gut microbiome composition. Here, we compared the microbiomes of wild and captive Comal Springs riffle beetles (Heterelmis comalensis) by … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
4
3

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 36 publications
0
4
3
Order By: Relevance
“…In the microbiome of captive individuals, we saw only a significant, but relatively small, reduction in Staphylococcus, which has been previously part of the natural microbiome of the sharpshooter, Acrogonia citrina [112]. In contrast to our findings, Staphylococcus abundance was found to be higher in abundance in captive beetles compared to their wild counterparts [98].…”
Section: Captivity May Lead To Differences In Both the Myco-and Micro...contrasting
confidence: 99%
See 1 more Smart Citation
“…In the microbiome of captive individuals, we saw only a significant, but relatively small, reduction in Staphylococcus, which has been previously part of the natural microbiome of the sharpshooter, Acrogonia citrina [112]. In contrast to our findings, Staphylococcus abundance was found to be higher in abundance in captive beetles compared to their wild counterparts [98].…”
Section: Captivity May Lead To Differences In Both the Myco-and Micro...contrasting
confidence: 99%
“…Many studies have reported microbial community differences related to captivity in mammals [92,93], birds [94,95], amphibians [96,97], and also in insects including beetles [98], armyworms [99], and fruit flies [100]. Often these studies report a reduction of alpha diversity [101, 102], which we did not observe here; instead we found a reduction of specific ASVs associated with captivity (Figure 3).…”
Section: Captivity May Lead To Differences In Both the Myco-and Micro...contrasting
confidence: 43%
“…Many studies have reported microbial community differences related to captivity in mammals ( 69 , 70 ), birds ( 71 , 72 ), amphibians ( 73 , 74 ), and also insects including beetles ( 75 ), armyworms ( 76 ), and fruit flies ( 77 ). Often, these studies report a reduction of alpha diversity ( 78 , 79 ), which we did not observe here; instead, we found a reduction of specific ASVs associated with captivity ( Fig.…”
Section: Discussionmentioning
confidence: 99%
“…This is consistent with previous observations in the field and laboratory that show COTS can survive for months without food (Birkeland & Lucas, 1990; Pearson & Endean, 1969; Yang et al, 2022). Changes in diet and the abiotic environment, which occurs when translocated into captivity, may also result in changes in the COTS microbiome (Jackson et al, 2018; Karl et al, 2018; Ley et al, 2008), as captivity shifts the composition and diversity of the microbiome in a variety of animals (Dallas & Warne, 2022; Isaacs et al, 2009; Kueneman et al, 2022; Madden et al, 2022; Mays et al, 2021; McKenzie et al, 2017; Ning et al, 2020; San Juan et al, 2021; Zhou et al, 2022). Changes in microbial and viral communities in captive COTS were not assessed here but may contribute to the observed transcriptional changes.…”
Section: Discussionmentioning
confidence: 99%